2018
DOI: 10.5513/jcea01/19.3.2168
|View full text |Cite
|
Sign up to set email alerts
|

Cherry tomato productivity as influenced by liquid organic fertilizer under different growth conditions

Abstract: This study was carried out to examine the impact of liquid organic fertilizer Ergonfill (LFE) on the yield and quality of cherry tomato (Lycopersicon esculentum Mill. Sakura F1) under different growth conditions. The experiment was set up in a randomized blocks design with four variants in three replications. Experiment variants were as follows: drought-stressed seedlings with and without LFE treatment, and non-stressed seedlings with and without LFE treatment. Exposure of cherry tomato seedlings to controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…LOF is a fertilizer that is more easily absorbed by roots and efficient in the application. The results study reported by Murtic et al (2018) showed that LOF could increase total soluble solids, total phenolics, total flavonoids, and total antioxidants in tomatoes. The combination of LOF and PGR can provide benefits for the growth and production of tomato.…”
Section: Introductionmentioning
confidence: 91%
“…LOF is a fertilizer that is more easily absorbed by roots and efficient in the application. The results study reported by Murtic et al (2018) showed that LOF could increase total soluble solids, total phenolics, total flavonoids, and total antioxidants in tomatoes. The combination of LOF and PGR can provide benefits for the growth and production of tomato.…”
Section: Introductionmentioning
confidence: 91%
“…Banyaknya jumlah klorofil pada daun dalam proses fotosintesis pada tanaman tomat cherry tidak berjalan secara maksimal. Akibat kekurangan kandungan nitrogen (N) mengakibatkan menurunnya aktivitas metabolisme tanaman yang dapat menimbulkan klorosis (Murtic et al 2018). Begitu pula fosfor (P) dan kalium (K) berperan dalam pertumbuhan vegetatif maupun generatif dalam membantu perkembangan batang (Naibaho et al, 2012).…”
Section: Drip Irrigation System Tomat Cherryunclassified
“…Tomatoes unlike other vegetables, are heavy feeder and perform better when provided with plenty of nutrients to grow better. Water soluble fertilizers (WSF) are used as chemical fertilizer in sprinkler or drip irrigation systems and for foliar spray to augment yield and to improve quality of fruits and vegetable crops [4][5][6][7][8][9]. These fertilizers are generally considered 100% soluble in water.…”
Section: Introductionmentioning
confidence: 99%